2020
DOI: 10.1186/s12885-020-6577-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of metastatic colorectal cancer treatment pathways and early clinical experience of trifluridine/tipiracil in the UK named patient programme

Abstract: Background: The standard first-and second-line chemotherapy backbone regimens for metastatic colorectal cancer (mCRC) are 5-fluorouracil (5-FU)/capecitabine-based with addition of irinotecan or oxaliplatin. Until recently, evidence for optimal sequencing post second-line was sparse. Trifluridine/tipiracil (indicated for mCRC and gastric cancer after standard chemotherapies) was made available to UK patients via a named patient programme (NPP) before receiving marketing authorisation in Europe in 2016, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Several other real-world studies assessing trifluridine/tipiracil in mCRC have also included patients with ECOG PS 2. [10][11][12][13][14][15] Our findings are keeping with the existing literature showing that patients with borderline performance status do not experience added toxicity from trifluridine/tipiracil 12 but seem to have worse survival outcomes. 11,13,14 The type of previous lines of treatment was another point of divergence between our study and the RECOURSE trial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several other real-world studies assessing trifluridine/tipiracil in mCRC have also included patients with ECOG PS 2. [10][11][12][13][14][15] Our findings are keeping with the existing literature showing that patients with borderline performance status do not experience added toxicity from trifluridine/tipiracil 12 but seem to have worse survival outcomes. 11,13,14 The type of previous lines of treatment was another point of divergence between our study and the RECOURSE trial.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with several other real-world studies. [10][11][12]15,20 The use of granulocyte colony stimulating factor was found to vary among different centres and is at the discretion of the treating physician. The most frequent non-haematological toxicities were fatigue and gastrointestinal symptoms such as nausea, diarrhoea and vomiting and were mild in the vast majority of patients both in the real-world and trial setting.…”
Section: Discussionmentioning
confidence: 99%
“…The improved treatment outcomes in randomized trials are sometimes hard to achieve in everyday clinical practice; thus, observational studies and retrospective analyses are often needed to assess the effects of anti-cancer drugs in the real-life setting. In clinical trials TT demonstrated a beneficial effect on PFS and OS in patients with mCRC refractory to standard chemotherapy (9)(10)(11)(12)(13)(14)(15). In randomized phase III clinical trial (RESOURCE)…”
Section: Discussionmentioning
confidence: 99%
“…It is considered the fourth leading cause of cancer‐related deaths across the world according to the World Health Organization (WHO) 2 . Because it became a necessity to improve the prognosis of CRC patients, accordingly the search for combinational therapeutic strategies evoked to be a demanding need aiming to increase the curing rate of the disease 3 …”
Section: Introductionmentioning
confidence: 99%